Rights of Passage: The Intersecting of Environmentalism, Arctic Sovereignty, and the Law of the Sea, 1968–82 - Meren, David; Plumptre, Bora (Journal of Canadian Studies/Revue d'études canadiennes, 2013)
This essay brings environmental and diplomatic history into conversation in order to examine the Trudeau government’s response to the 1969–70 voyages of the oil tanker Manhattan through the Northwest Passage. By passing the Arctic Waters Pollution Prevention Act and extending Canada’s territorial sea to 12 miles, Ottawa successfully instrumentalized the heightened environmental concern of the period in order to press Canadian claims to sovereignty in the Arctic. The essay demonstrates that this custodial approach was consistent with the functionalist tradition in Canadian liberal internationalism. More broadly, it reveals the promise of re-examining Canadian international history through the prism of environmental history.